Kajian Kritis terhadap Kitab Tafsir Syaikh Uthaimin, Menganalisis Pendekatan dan Metodologi Tafsirnya - Alif Hibatullah; Alghaniy Pramudya Rizasawan; Johana Salsabillah; Abu Bakar (Jurnal Syntax Admiration, 2024)
A critical study of Shaykh Uthaimin's tafsir is an in-depth attempt to analyze the approach and methodology of exegesis used by this figure. Shaykh Uthaimin, a famous scholar, is known for his work that includes Quranic exegesis. This study explores in detail his famous tafsir, "Tafsir Ahkam min al-Qur'an min al-Karim," focusing on his approach and method. The bi al-Ma'thur tafsir and Tahlili tafsir approaches, used by Shaykh Uthaimin, became the focal point of the analysis. This study explores how this method is reflected in the interpretation of surah al-Fatihah, al-Baqarah, and surah Ali Imran verse 29. The ahkam style applied by Uthaimin is also an important part of this critique, with a broader understanding of the Shari'a, its benefits, and the law of wisdom. This study not only limits itself to elements of Sharia law in the interpretation of certain verses, but also covers the entire Qur'an. In particular, this study highlights Uthaimin's view of the basmalah in surah al-Fatihah and its implications for prayer. Overall, this critical study provides in-depth insight into Shaykh Uthaimin's approach and methodology of exegesis, opening up space for a better understanding of his contribution to understanding and explaining the Qur'an.